Implementation of Electronic Health Records in US Nursing Homes. Issue 8 (August 2017) - Bjarnadottir, Ragnhildur I.; Herzig, Carolyn T.A.; Travers, Jasmine L.; Castle, Nicholas G.; Stone, Patricia W.
Abstract : While electronic health records have emerged as promising tools to help improve quality of care, nursing homes have lagged behind in implementation. This study assessed electronic health records implementation, associated facility characteristics, and potential impact on quality indicators in nursing homes. Using national Centers for Medicare & Medicaid Services and survey data for nursing homes, a cross-sectional analysis was conducted to identify variations between nursing homes that had and had not implemented electronic health records. A difference-in-differences analysis was used to estimate the longitudinal effect of electronic health records on commonly used quality indicators. Data from 927 nursing homes were examined, 49.1% of which had implemented electronic health records. Nursing homes with electronic health records were more likely to be nonprofit/government owned ( P = .04) and had a lower percentage of Medicaid residents ( P = .02) and higher certified nursing assistant and registered nurse staffing levels ( P = .002 and .02, respectively). Difference-in-differences analysis showed greater quality improvements after implementation for five long-stay and two short-stay quality measures ( P = .001 and .01, respectively) compared with those who did not implement electronic health records. Implementation rates in nursing homes are low compared with other settings, and better-resourced facilities are more likely to have implemented electronic health records. Consistent with other settings, electronic health records implementation improves quality in nursing homes, but further research is needed to better understand the mechanism for improvement and how it can best be supported.